2022
DOI: 10.1186/s12879-022-07777-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating methodological approaches to assess the severity of infection with SARS-CoV-2 variants: scoping review and applications on Belgian COVID-19 data

Abstract: Background Differences in the genetic material of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants may result in altered virulence characteristics. Assessing the disease severity caused by newly emerging variants is essential to estimate their impact on public health. However, causally inferring the intrinsic severity of infection with variants using observational data is a challenging process on which guidance is still limited. We describe potential limitations and biases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…We are confident that the Belgian national surveillance data reflects our catchment area’s epidemiology, as shown in another project published by our group recently [ 29 ]. We were also reassured to read a recent paper by Meurisse et al [ 11 ], who found that exposure ascertainment based on time periods leads to the most precise results when studying severity per variant wave. We, therefore, chose periods in which each variant was circulating at levels of at least 80%, based on national COVID-19 surveillance data.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We are confident that the Belgian national surveillance data reflects our catchment area’s epidemiology, as shown in another project published by our group recently [ 29 ]. We were also reassured to read a recent paper by Meurisse et al [ 11 ], who found that exposure ascertainment based on time periods leads to the most precise results when studying severity per variant wave. We, therefore, chose periods in which each variant was circulating at levels of at least 80%, based on national COVID-19 surveillance data.…”
Section: Discussionmentioning
confidence: 91%
“…The inclusion periods were defined as the periods in which one particular strain of the SARS-CoV-2 virus accounted for 80% or more of the circulating viruses in Belgium [ 11 ]. We identified four periods of interest, shown below, based on the Belgian epidemiology; the Beta VOC did not reach 80% dominance at any point and was therefore not included.…”
Section: Methodsmentioning
confidence: 99%
“…First, in the main analysis, the variant of infection was assigned based on linkage with WGS-confirmed lineage data from the COVID-19 TestResult database. This might result in selection bias and drastically limits the sample size [ 43 ]. The small sample sizes reduce the statistical power and the reliability of significant findings [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying missing data mechanism is unknown. Sixth, different selection steps were performed to obtain data of our study population (i.e., selection of patients tested for COVID-19, treated in the hospital for COVID-19 symptoms, registered in the CHS, and with an Omicron BA.1, BA.2, or BA.4/5 infection identified by linking WGS-confirmed lineage data) [ 43 ]. Hence, patients in our study population might have specific characteristics distinctive from the population of all hospitalized patients in Belgium and the general population, thereby limiting generalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation